Faith Over Distance: The Christian Ethical Response to Phone Sex in Marital Long-Distance Relationships - Simon, Simon; Yulianto, Auw Tammy; Pararem, Elsyina Rode; Tanhidy, Jamin (UIN Sunan Gunung Djati Bandung, 2023)
This study delves into the ethical considerations of phone sex within long-distance marital relationships (LDRs) from a Christian ethical perspective. Employing qualitative methods, including scriptural analysis and literature review, the research aims to ascertain the compatibility of phone sex with Christian doctrinal teachings concerning marital intimacy. The findings suggest that phone sex is perceived as diverging from the Christian ethical norms which advocate for physical and personal marital interactions, categorizing it as a form of sexual perversion akin to masturbation. The study contributes to theological discourse by providing a framework for understanding modern challenges in marital intimacy within the Christian context. It emphasizes the importance of maintaining physical intimacy as prescribed by scripture and highlights the potential spiritual and ethical pitfalls associated with phone sex in LDRs. Recommendations include fostering educational and counseling initiatives within church communities to guide couples in navigating these issues. This study enriches the dialogue on integrating technology into marital practices while adhering to Christian ethical standards.